Cariprazine in the Treatment of Bipolar Disorder: Within and Beyond Clinical Trials - Do, André; Keramatian, Kamyar; Schaffer, Ayal; Yatham, Lakshmi (Frontiers in Psychiatry, 2021)
Bipolar disorder (BD) is chronic psychiatric disorder associated with significant impairment in psychosocial functioning and quality of life. Although current pharmacological treatments for BD have improved its clinical management, many patients do not achieve remission, particularly those suffering from bipolar depression. In addition, available treatments are associated with a myriad of potential adverse effects, which highlights the need for novel therapeutic agents that can be effective for both phases of the illness with a reduced side effect burden. Cariprazine is a novel antipsychotic that is a dopamine D2/D3 partial agonist with a preference for D3 receptors. In this review, we examine the pharmacological properties, clinical efficacy and tolerability profile of cariprazine in patients with BD, taking into account the latest clinical trials data. We also review post hoc analyses addressing clinically relevant subgroups and symptom domains in BD. Current evidence suggests efficacy for cariprazine 3-12 mg/day in the treatment of acute manic and mixed episodes; for bipolar depression, the efficacy of cariprazine appears to be dose-related, with doses of 1.5-3 mg/day beneficial as monotherapy. Cariprazine is overall well-tolerated by patients in both manic and depressive episodes. Its most common side effects relative to placebo include akathisia, extrapyramidal symptoms and nausea. There are no metabolic concerns reported with cariprazine use. In summary, the latest evidence suggests that cariprazine is an effective and safe treatment option for BD.